(untitled) (Journal of the College of Education for Women, 2019)
The characteristic of our time is the tremendous technological progress and the wide use of the Internet. Children have had a large share of this progress.as they are becoming fond of having the technological equipment of tablets and mobile phones which become indispensable for these children cannot do without them .Recently, the phenomenon of using mobile phones and tablets by children has become more widespread, and the society in general and parents, in particular, have ignored the reasons for their health .Despite the many advantages and benefits for children who are well trained to use these devices properly that have enhanced their cognitive and social abilities, there are many disadvantages that could harm children’s growth if they are badly using or addicting to those Internet-related tablets .The aim of this study is to detect the negative effects of childhood addiction to tablets, as well as to identify the differences between children in their addiction to tablets according to the gender variable.The researcher has used the analytical descriptive method to form the research sample that consists of (300) children of both sex from the state kindergartens in the city of Baghdad -Karkh where they randomly selected, and the researcher has resorted to interviews with children to collect data .The most important findings of this study: -1. The addiction to tablets affects children greatly and causes them many health, psychological and social problems as its features have begun to appear on the children of our society.2. Females are more prone to using male tablet devices than males, as females have more time to play with these devices because they are limited to playing outside the home, unlike boys who go out to enjoy games that require a longer time out.The researcher has come out with many recommendations and proposals:1. Parents should limit their children’s addiction to tablet devices, trying to keep their children entertained by other recreational activities to reduce the hours they spend on tablet screens.2. Try to disconnect the devices for children from the Internet to avoid a lot of trouble and just download some of the games and videos that are popular for their children and that suit their age.3. Media must have attention to the phenomenon of addiction to the use of tablets and broadcast awareness programs to help reduce this phenomenon and find appropriate solutions.